Right-Wing Legal Mobilization Against Abortion. The Case of Poland - Kocemba, Karolina
Over the last few years, women’s rights and freedoms have been intensely challenged before the Constitutional Courts: in Poland, the Constitutional Court tightened pregnancy termination laws, the Constitutional Court in Bulgaria declared the anti-violence Istanbul Convention unconstitutional, the Constitutional Court in Croatia heard the case on pregnancy termination restriction, and in the United States, the Supreme Court overturned the famous abortion decision in the case of Roe v. Wade. We may see a specific pattern here: using the law, especially constitutional law and Constitutional Courts, to restrain women's rights without the support of most citizens. The ruling of the Polish Constitutional Court banning abortion on the grounds of fetal defects triggered one of the largest social protests in Poland since 1989. Since those are legal decisions, they are immune to the mass mobilization and protests they provoke. What is typical for all these cases is not only the limitation of women's rights. It is also the type of non-state actors that are pushing this type of agenda through legal mobilization. These were mostly fundamentalist and religious organizations. This paper aims to show the constitutive role of right-wing non-state actors and their legal mobilization for the erosion of reproductive rights using abortion in Poland as a case study. I conclude that these actors use liberal infrastructure of protecting fundamental rights and freedoms, such as constitutional courts and constitutional litigation, to restrict women's rights, and the key to success is the transnational cooperation of engaged actors.
Keywords: legal mobilization; strategic litigation; constitutionalism; populism; reproductive rights; human rights; women's rights